2009
DOI: 10.1002/hlca.200900140
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Towards Europium(III) of the Radiolysis Products of the Ionic Liquid 1‐Methyl‐3‐butyl‐1H‐imidazolium Bis[(trifluoromethyl)sulfonyl]amide (C4‐mimTf2N) and Effect of Water: A TRLFS (Time‐Resolved Laser‐Induced Fluorescence Spectroscopy) Preliminary Study

Abstract: Dedicated to Professor Jean-Claude Bünzli on the occasion of his 65th birthdayThe effect of laser irradiation at l exc 266 nm onto the fluorescence characteristics of Eu III in solution of the ionic liquid 1-methyl-3-butyl-1H-imidazolium bis[(trifluoromethyl)sulfonyl]amide (C 4 -mimTf 2 N) was examined for various amounts of H 2 O added. Stable radiolytic products that were generated at very low doses (in the range of 4 kGy) were very reactive with Eu III and led to the appearance of a new europium luminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(25 reference statements)
3
8
0
Order By: Relevance
“…For all the IL solutions, the remaining water content has been checked by IR (Bruker, Equinox 55, quartz cuvette, 1 cm pathway) at the end of the measurements, by comparison with the IR spectra of the three pure ILs before and after degassing. In agreement with previous works, , the water peak is present in the 5200–5350 cm –1 range for the three ILs. For the degassed samples, no significant amount of water could be detected.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…For all the IL solutions, the remaining water content has been checked by IR (Bruker, Equinox 55, quartz cuvette, 1 cm pathway) at the end of the measurements, by comparison with the IR spectra of the three pure ILs before and after degassing. In agreement with previous works, , the water peak is present in the 5200–5350 cm –1 range for the three ILs. For the degassed samples, no significant amount of water could be detected.…”
Section: Methodssupporting
confidence: 93%
“…The temperature was controlled at T = (18 ± 0.5) °C. Previous trials have shown that the Teflon caps are tight enough to prevent water from entering the IL samples, even for a long period of time (up to months) . UV–visible absorption spectra were recorded taking either pure acetonitrile or the corresponding pure degassed ILs as a reference for samples in acetonitrile or in ILs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…ILs unavoidably absorb H 2 O from the atmosphere and their average water content is about 200 ppm as purchased. Thus, ILs were dried under vacuum following a previously published procedure [38] prior to sample preparation. Due to their hydrophobicity, they can be dried to very low final water contents (20 ppm) prior to mixing.…”
Section: Experimental Section Reagentsmentioning
confidence: 99%
“…) was purchased from Solvionic, Verniolle, France (purity: 99.5%) and dried in vacuum at a raised temperature of 60 ¡ 1 uC prior to use, according to a previously published procedure. 19 Europium nitrate hexahydrate was obtained from Riedel-de Haen and HNO 3 was from Merck (conc. 65%).…”
Section: Introductionmentioning
confidence: 99%